2017
DOI: 10.1177/1010428317700002
|View full text |Cite
|
Sign up to set email alerts
|

Plasma fibrinogen level may be a possible marker for the clinical response and prognosis of patients with breast cancer receiving neoadjuvant chemotherapy

Abstract: Neoadjuvant chemotherapy has been established as standard treatments for advanced breast cancer among multidisciplinary therapies. A simple and instructive biomarker for the postoperative recurrence and metastasis is needed to evaluate the therapeutic effect. Plasma fibrinogen level has been shown to be associated with tumor progression and poor outcomes in breast cancer patients. This study aims to further evaluate the clinical and prognostic value of plasma fibrinogen level as a biomarker in breast cancer pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…The close correlation between inflammation and tumorigenesis may be the main possible explanation for the prognostic role of serum Alb in various malignancies [15]. Elevated serum Fib has also been indicated as a predictor for poor prognosis in esophageal cancer [23], breast cancer [24] and EOC [25]. Increased plasma fib expression contributes to elevated blood coagulability state and promotes the intravasation, adhesion and survival of tumor cells, which results in increased metastatic potential in cancer model [26].…”
Section: Discussionmentioning
confidence: 99%
“…The close correlation between inflammation and tumorigenesis may be the main possible explanation for the prognostic role of serum Alb in various malignancies [15]. Elevated serum Fib has also been indicated as a predictor for poor prognosis in esophageal cancer [23], breast cancer [24] and EOC [25]. Increased plasma fib expression contributes to elevated blood coagulability state and promotes the intravasation, adhesion and survival of tumor cells, which results in increased metastatic potential in cancer model [26].…”
Section: Discussionmentioning
confidence: 99%
“…CA125 is a common blood marker tested in breast cancer and ovarian cancer and it allows for the identification and distinction of the plasma from BCa patients [76,77]. Although the plasma fibrinogen level may be considered a possible marker for the clinical response and prognosis of patients with breast cancer [78], we were able to observe a slightly increased fibrinogen level in our BCa samples, but not enough to be significant in the samples used in our studies. This similarly allows for a more relevant comparison among the HuP3D cultures using either healthy or BCa patient plasma.…”
Section: Discussionmentioning
confidence: 52%
“… 29 Fibrinogen (FIB) is a kind of clotting factor 30 and has been proven to have prognostic value in breast cancer. 31 Here, we first reported that the PT (%), PT (sec) and FIB could serve as independent risk factors for prediction of RFS.…”
Section: Discussionmentioning
confidence: 91%